The Jewish Middle Ages - Bakhos, Carol; Langer, Gerhard, 1960- (SBL Press, 2023)
"For many, the Middle Ages in general evokes a sense of the sinister and brings to mind a world of fear, superstition, and religious fanaticism. For Jews it was a period marked by persecutions, pogroms, and expulsions. Yet at the same time, the Middle Ages was also a time of lively cultural exchange and heightened creativity for Jews. In The Jewish Middle Ages, contributors explore the ways in which the stories of biblical women, including, Eve, Sarah, Hagar, Rebekah, Zipporah, Ruth, Esther, and Judith, make their way into the rich tapestry of medieval Jewish literature, mystical texts, and art, particularly in works emanating from Ashkenazic circles"-- Provided by publisher.
Keywords: Bible. -- Old Testament -- Criticism, interpretation, etc., Jewish -- History -- To 1500.; Bible -- Influence -- Medieval civilization.; Bible -- Influence -- Civilisation médiévale.; Women in the Bible.; Women in Judaism -- Europe -- History -- To 1500.; Judaism -- Europe -- History -- To 1500.; Jews -- History -- 70-1789.; Middle Ages.; Juifs -- Histoire -- 70-1789.; Moyen Âge.; Femmes dans la Bible.; Judaïsme -- Europe -- Histoire -- Jusqu'à 1500.